Superstition as Seen in Mark Twain s The Adventures of Tom Sawyer - Ira Marlina Tulis; Ceisy N. Wuntu; Agustine C. Mamentu (English Education Postgraduate Program, Universitas Negeri Manado, 2023)
This research aims to find out how superstitions are revealed in The Adventures of Tom Sawyer and how the impact of superstitions on the main character by applying qualitative research where data is collected in the form of words and quotes from novels books dictionaries and journals to strengthen the research The researcher collected data using two types of sources namely primary sources and secondary sources Primary sources are taken from the novel itself and secondary sources are taken from books dictionaries and relevant journals In analyzing the data the author uses an objective approach whose research is solely based on Intrinsic criteria The results of this research show that there are four categories of superstition revealed in The Adventures of Tom Sawyer namely believing in superstitious rituals believing in magic believing in urban legend and believing in amulets In addition this research also shows that superstition brings positive and negative impacts on Tom Sawyer the main character in the story The positive impact found is that superstition can provide a sense of security and cause obedience to Tom Sawyer While the negative impact is that superstition makes Tom sacrifice himself and brings disappointment because what Tom expects does not match the reality that occurs < em>< p> nbsp;< em>< p>